2018
DOI: 10.1111/acps.12872
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor (BDNF) in children with ASD and their parents: a 3‐year follow‐up

Abstract: Our results contradict those from recent published meta-analyses with the age, the presence of ID and allergies being possible contributing factors. The parents' data indeed point to a role of BDNF in the pathophysiology of ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 56 publications
0
11
0
1
Order By: Relevance
“…Recently, de novo mutations in TrkB were identified in individuals with ASD [55]. Abnormal BDNF levels in the cortex [37], hippocampus [37], striatum [3536], and serum [56] were reported in ASD. The results of those studies suggest that the BDNF and TrkB receptor system correlates with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, de novo mutations in TrkB were identified in individuals with ASD [55]. Abnormal BDNF levels in the cortex [37], hippocampus [37], striatum [3536], and serum [56] were reported in ASD. The results of those studies suggest that the BDNF and TrkB receptor system correlates with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical data on neurotrophic factor levels in children with ASD have yielded inconsistent results. One study showed that the serum BDNF levels of children with ASD were significantly higher than that of the control subjects 13 , whereas Makkonen et al 14 suggested that was no significant difference in serum BDNF concentrations between cases and controls, and another study showed that BDNF serum levels were significantly decreased in ASD children when compared with controls 15 . For VEGF, results from Emanuele et al showed that VEGF levels in patients with ASD were lower than that of healthy controls 16 .…”
Section: Shu-han Liu Xiao-jie Shi Fang-cheng Fan and Yong Cheng *mentioning
confidence: 99%
“…Furthermore, Bryn et al 30 found increased plasma levels of BDNF in children with ASD compared with age-and sex-matched controls, observing that BDNF levels were particularly high in children with intellectual disability. In addition, all ASD patients enrolled in studies whose results revealed normal or low BDNF levels were intellectually normal or had, at least, an IQ over 70 24,27 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this assumption, a growing number of articles, reviews and meta-analysis have appeared evaluating the possible changes in BDNF blood levels in ASD [19][20][21][22] . However, the results of the studies have been inconsistent, some evidencing reduced BDNF serum [23][24][25][26][27] , while a larger number of other studies have shown elevated BDNF serum levels in children with ASD as compared to healthy controls 8,11,20,[28][29][30][31][32] . Additionally, studies evaluating levels of BDNF in neonates who subsequently evolved to an ASD also revealed inconsistent results [33][34][35][36][37][38] .…”
mentioning
confidence: 99%